2005
DOI: 10.1063/1.2125728
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the ionic and electronic density profiles in liquid metal surfaces

Abstract: First principles molecular dynamics simulations have been performed for the liquid-vapor interfaces of liquid Li, Mg, Al and Si. We analize the oscillatory ionic and valence electronic density profiles obtained, their wavelengths and the mechanisms behind their relative phase-shift.PACS numbers: 61.25. Mv, 64.70.Fx, 71.15.Pd X-ray reflectivity measurements on the surface of liquid metals and alloys, along with other techniques like diffuse scattering or grazing incidence diffraction, have shown the existenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…In previous studies concerning the ionic DP in a wide range of simple liquid metals, we found a linear relationship between the wavelength of the ionic oscillations and the radii of the associated Wigner-Seitz spheres [46]. We have verified that this relationship is also fulfilled by the previous calculated value of 2.82 Å.…”
Section: Results: the Free Liquid Surfacesupporting
confidence: 85%
“…In previous studies concerning the ionic DP in a wide range of simple liquid metals, we found a linear relationship between the wavelength of the ionic oscillations and the radii of the associated Wigner-Seitz spheres [46]. We have verified that this relationship is also fulfilled by the previous calculated value of 2.82 Å.…”
Section: Results: the Free Liquid Surfacesupporting
confidence: 85%
“…At larger distances from the interface, details of the specific interactions between the ions and the solid play a minor role. As for most other isotropic liquids, from the third layer on, interfacial profiles are quantitatively described by generic mean-field models. In this regime, for most liquids, the structure at buried solid/liquid interfaces and the free surface is determined by bulk parameters, namely, the dominating length scale d b and the decay length ξ b of the bulk’s correlation function. Indeed, X-ray reflectivity experiments indicate that for a wide range of commonly used anions and cations in this respect ILs do not behave differently compared to the mere of other standard liquids . , In neat bulk IL, Triolo et al showed that imidazolium-based ILs with cations featuring long aliphatic side chain exhibit long range density fluctuations in X-ray scattering that correlate with the length of the hydrocarbon chain. Similarly, Nishi et al , studied the gas/IL interface and showed that an ordered interfacial structure evolves because of interfacial pinning of bulk density fluctuations, without extended lateral ordering within the layering .…”
Section: Introductionmentioning
confidence: 99%
“…However, this explanation has recently been questioned and, based on ab initio results for several liquid metals, a different cause has been proposed. 41 Specifically it hinges on the interplay between the width ͑͒ of the pseudoatomic valence density and the separation of layers ͑͒ in the ionic DP. Indeed, three broad groups were identified: ͑i͒ those with a ratio of 0.62Յ / Յ0.64, where the ionic and electronic DPs oscillated in the opposite phase ͑i.e., the alkalis͒, ͑ii͒ those with 0.44Յ / Յ0.47 had ionic and electronic DPs nearly in phase ͑i.e., Tl and Si͒, and ͑iii͒ those with 0.55Յ / Յ0.59 which showed an intermediate behavior ͑i.e., Mg, Ba, and Al͒.…”
Section: Results: Liquid-vapor Interfacementioning
confidence: 99%
“…Parenthetically, this explanation has also accounted for the variety of relative phases between the ionic and valence electronic density profiles obtained for the LV interface in a wide range of simple liquid metals. 41 From the previous density profiles, we have evaluated the total electronic density profile ͑which is the physical magnitude probed in the x-ray reflectivity measurements͒ and therefrom the associated reflected intensity R͑q z ͒. This latter step involves accounting for the surface roughness c , which appears in the form of a Debye-Waller-type factor ͓see Eq.…”
Section: Discussionmentioning
confidence: 99%